Free Fatty Acid Composition of Akakatik Cheese, A Traditional Turkish Dairy Product - Simsek, B.; Gun, I. (Asian Journal of Chemistry, 2010)
Akçakatik cheese is one of the most popular varieties of cheese manufactured in some provinces in the Mediterranean of Turkey. In this study, fatty acid composition of Akçakatik cheese was analyzed by gas chromatography. The characteristics of the chromatographic profiles were studied by principal components and linear discriminant analyses were performed. The mean values for chemical properties of Akçakatik cheese were pH 5.121 ± 0.140; titratable acidity 0.866 ± 0.302 %; TS 73.960 ± 7.736 %; fat content 25.522 ± 5.456 %; salt content 0.409 ± 0.084 %. The saturated fatty acid, total unsaturated fatty acid, monounsaturated fatty acid, polyunsaturated fatty acid of samples were found as 61.87 ± 4.067, 33.246 ± 2.919, 30.728 ± 2.648 and 2.519 ± 0.516 %, respectively. Palmitic acid levels were found to be the highest of the saturated fatty acid in all samples. Oleic acid content in all cheeses was also considerable higher than those of other unsaturated fatty acids.